Data Visualization Camp Instructional Materials (2017-18) - (:unkn) unknown (My University, 2017)
These materials are from the 2017 Data Camp on data visualization held at UWM Libraries. The one-hour workshop covers how to chose the right chart for your data and how to streamline that chart to best tell your story. The materials work for both librarians and members of the university community. Materials include a presentation file (with supplemental notes), one informational handout, and two activity handouts. Please refer to the book [Evergreen, S. D. H. (2017). Effective data visualization: The right chart for the right data. SAGE Publications.] for background information for this workshop. Materials from the 2018 Data Visualization Workshop (Data Visualization 201) were added in July 2021.
Keywords: data camp; data management; research data management; data services; research data; data information literacy; visualization; data visualization